Self-management: keeping it simple with “Flo” - Cund A; Birch-Jones JL; Kay M; Connolly P (Dove Medical Press, 2015)
Audrey Cund,1–4 Jayne L Birch-Jones,1,3,4 Martin Kay,1 Patricia Connolly4 1School of Health, Nursing and Midwifery, University of The West of Scotland, Paisley, Scotland, UK; 2Nottinghamshire Health and Social Care Assistive Technology Programme, Mansfield and Ashfield Clinical Commissioning Group, National Health Service, Rainworth, Mansfield, Nottinghamshire, UK; 3Kay Consultancy Ltd, Newark, UK; 4Department of Biomedical Engineering, University of Strathclyde, Glasgow, Scotland, UK Background: Living with and managing a long-term condition are complex processes that are further compounded by a range of medical and psychosocial factors. The size and scale of long-term conditions in the UK is vast, with strategic drivers seeking to find innovative ways to managing this problem. Methods: This project introduced Simple Telehealth “Florence,” a software-based short message service texting system to monitor a variety of conditions, such as diabetes, hypertension, and wounds, initially in one region of the East Midlands, England, UK. This article discusses the findings from our patient and staff evaluations of using the system. In total, 37 patients across four conditions, diabetes, chronic obstructive pulmonary disease, hypertension, and Asperger's syndrome, evaluated the study and this exercise involved 33 nurses in teams across three locations over a 6-month period. Evaluation was made using a simple, self-completed questionnaire and analysis of qualitative comments. Results: The majority of patients find the service easy to use, reassuring, and reducing the number of contacts they had with their doctor. The results also show that staff did notice a reduction in consultation time, highlighting the potential of the system to save time; the majority viewed it as a support to existing approaches aimed at the management of long-term conditions. Discussion: This study adds to the growing body of evidence that supports community nurses through the use of innovative ways to assess, support, and monitor long-term conditions. It also offers insight into the experience of patients and staff working together in one region of England, UK. Recommendations: Embedding Simple Telehealth “Florence” as an option within primary care services in the UK is hereby proposed. This would add to the range of options and therapeutic approaches available through modern Telehealth. Keywords: self-management, simple telehealth, Flo, patient experience, community nurse